Politik dan Konservatisme Islam: Indonesia dan Tunisia - Budi Juliandi; Basri Ibrahim; Saifuddin Herlambang (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Conservatism is needed to maintain harmony in the Muslim community. Conservatism, therefore, is not always negative. However, facing a public opinion controlled by conservative forces, is much more difficult than facing a despotic political force. This paper shows that politics has defied Islamic conservatism in Indonesia and Tunisia. Conservatism ridden by politics causes communal violence that not only destroys one's reputation, but also a moderate understanding of Islam. This paper reinforces Hamayotsu’s (2014) assertion that political competition among elites over distribution of state resources, land, ethnicity and other identities were the primary cause of the conflict. Instead, this paper addresses the statement of Christoper Duncan (2014) which states that the essential source and character of the communal violence is religion.